PENGARUH ETIKA PROFESI AKUNTAN DAN TEKANAN KETAATAN TERHADAP KUALITAS PELAPORAN KEUANGAN DENGAN KUALITAS SISTEM PENGENDALIAN INTERNAL SEBAGAI VARIABEL MODERASI (STUDI KASUS PT BANK MANDIRI TBK) - Manurung, Haris - (JOURNAL OF BUSINESS STUDIES, 2025)
This study aims to examine the impact of Accounting Professional Ethics and Compliance Pressure on the Quality of Financial Reporting, with the Quality of Internal Control Systems (ICS) as a moderating variable. The research focuses on the banking sector, specifically PT Bank Mandiri (Persero) Tbk, to evaluate how internal and external pressures interact with ethical standards. The results indicate that Accounting Professional Ethics contributes significantly and positively to the quality of financial reporting. Conversely, Compliance Pressure exerts a negative impact, potentially compromising reporting integrity. Furthermore, the analysis reveals that a high-quality Internal Control System acts as a robust moderator; it amplifies the positive influence of ethical behavior and effectively mitigates the adverse effects of compliance pressure.These findings underscore the critical necessity of reinforcing ethical frameworks and strengthening internal control mechanisms within accounting practices. For institutions like PT Bank Mandiri Tbk, prioritizing these elements is essential to safeguard the transparency and optimal quality of financial disclosures.